Gereja Virtual dan Tantangan Pascamodernisme: Suatu Analisis Eklesiologis dari Perspektif Reformasi - Tirtanadi, Rendy; Silalahi, Frans (STT Reformed Injili Internasional, 2025)
This article examines the phenomenon of the virtual church in the postmodern era marked by pluralism, relativism, and digitalization. It explores the extent to which virtual church practices are compatible with sixteenth-century Reformation ecclesiology. Drawing on the ecclesiological principles of Martin Luther and John Calvin, the study finds that both Reformers understood the church as a visible community constituted through the proclamation of the Word and the administration of the sacraments, which inherently presuppose physical fellowship. Even so, digital technology holds significant instrumental value for teaching, pastoral care, and congregational communication. Consequently, virtual church expressions may serve as supplementary means of ministry but cannot replace the physical church as the true ecclesial community. The study highlights the need for a discerning and theologically grounded integration of technology in contemporary church practice.